Digital Technology Usage as a Correlate of InSchool Adolescents‟ Risky Sexual Behaviour in Federal Capital Territory (FCT), Abuja - Andrew Nonso, Udenka; Joy I. , Anyanwu; Ogwa Adikwu, Victoria; Imah, EmeEtop; Sunday Otu, Mkpoikanke (International Journal of Psychosocial Rehabilitation, 2021)
The study sought to determine the relationship between digital technology usage and risky sexual behaviour of in-school adolescents in Gwagwalada Area Council. The study adopted correlational survey design. The main purpose of the study was to find out the relationship between digital technology usage and in-school adolescent risky sexual behaviour. The population for the study is 1693 research elements from public schools. It consists of 873 females and 820 males. A total of 253 respondents were randomly selected from public secondary schools consisting 135 females and 118 males drawn from 5 public secondary schools in Gwagwalada Area Council using simple random sampling technique. Two research questions and two hypotheses guided the study. The instrument used for the collection of data was digital technology usage as correlate of in-school adolescent risky sexual behaviour questionnaire (DTUC1ARSBQ). The reliability of the instrument was carried out using Cronbach alpha. The data was collected through the help of two research assistants. The research questions were answered using regression analysis at 0.05. The study reported that there is a high positive relationship between digital technology and in-school adolescent risky sexual behaviour. The study also discovered that digital technology was responsible for the in-school adolescent risky sexual behaviour. That there is a significant relationship between digital technology usage and in-school adolescents’ risky sexual behaviour, F(1,448)=952.287, p=0.000. That both in-school adolescent boys and girls are affected by the use of digital technology among others. It was recommended that parents and teachers should monitor the internet cites the in-school adolescents visit in order to reduce their risky sexual behaviours.